Penerapan Internet of Things Berbasis Teknologi Voice User Interface Untuk Kendali Jarak Jauh Dengan Node MCU 8266 Pada Rumah Pintar - Arif Harbani; Rizal Himawan Fassa (Universitas Binaniaga Indonesia, 2022)
Smart Home is a residence or residence that connects a communication network with electrical equipment that is possible to be controlled, monitored or accessed remotely. Smart home can also increase efficiency, convenience and security by using technology automatically. This study builds an IoT-based Smart Home using voice on Google Assistant. This is needed as a solution for sick people who are in wheelchairs/beds or people with disabilities but can speak or elderly people who cannot reach the switch to turn on/off household appliances. In addition, in order to be able to control home devices from a very long distance. Google Assistant converts voice commands to text. The text is then forwarded from Google Assistant to Webhooks by IFTTT. In testing the system has succeeded in turning on and off electrical equipment with voice commands using Google Assistant. A more effective prototype has been produced based on the results of testing to experts it is obtained